Effects of a GaN cap layer on the reliability of AlGaN/GaN Schottky diodes. Issue 5 (14th January 2015) - Kang, He; Wang, Quan; Xiao, Hongling; Wang, Cuimei; Jiang, Lijuan; Feng, Chun; Chen, Hong; Yin, Haibo; Qu, Shenqi; Peng, Enchao; Gong, Jiamin; Wang, Xiaoliang; et al.
<x xml:space="preserve">Abstract</x> In this paper, AlGaN/GaN‐ and GaN/AlGaN/GaN‐based Schottky barrier diodes (SBDs) were fabricated and studied for comparison. The recorded electrical characteristics of the devices show that the introduction of a GaN cap layer can evidently reduce the reverse leakage current and suppress the forward current decay of the devices. What is more important, the GaN/AlGaN/GaN‐based SBDs are capable of greatly alleviating the unrecoverable degradation of the reverse characteristics, which was observed in the device without a GaN cap layer when the device was under long time reverse dc stress. Detailed analyses were discussed.